Характерні риси діяльності IT-підприємств: обліковий аспект - Лоскоріх Габріелла; Gabriella Loskorikh; Loszkorih Gabriella (Національний авіаційний університет, 2021)
Резюме. Актуальність статті обґрунтовано зростаючими показниками сфери ІТ. Для узгодження категоріального апарату розкрито сутність понять, які виступають результатом діяльності ІТ-підприємства («ІТ-послуга», «ІТ-продукти» та «ІТ-товар»), з позиції відображення їх в обліку. Підтверджено неможливість їх ототожнення, оскільки вони мають різні облікові наслідки як для ІТ-підприємства, так і для замовника залежно від умов договору та цілей подальшого використання. Обґрунтовано необхідність глибоких знань у бухгалтера, який працює в ІТ-сфері. Узагальнено помилки, яких припускаються бухгалтери, якщо їхня підготовка у цій сфері здійснена на неналежному рівні. Визначені характерні риси діяльності ІТ-підприємств (масштабованість, значні ризики, високий рівень плинності кадрів) висувають додаткові вимоги до організації обліку. Відображено напрями, які потребують найбільшої уваги, для створення належного інформаційного забезпечення управління діяльністю ІТ-підприємства.

Abstract. The relevance of the article is justified by the growing indicators of the IT sector. Despite the quarantine restrictions, most IT companies are more profitable. However, the growth rate is lower than before quarantine. This requires special attention to the organization of information support of the management process, which would take into account the specific features of IT enterprises. The main purpose of the article is to determine the characteristics of IT companies that have a decisive influence on the organization of accounting in these companies. This goal is realized on the basis of the application of methods of observation, comparison, analysis, synthesis, generalization. To harmonize the categorical apparatus, the essence of the concepts that are the result of the activities of the IT enterprise – IT service, IT product and IT product, from the standpoint of their reflection in the account. The impossibility of their identification is confirmed. They have different accounting implications for both the IT company and the customer depending on the terms of the contract and the purposes of further use. The specific properties of IT services are characterized, which include: the complexity of the IT service; low level of consumer involvement in the process; remote interaction between manufacturer and user. The influence of these features on the organization of accounting is described, in particular, the organization of analytical accounting and the development of management reporting. The need for deep knowledge of an accountant working in the IT field is substantiated. The mistakes made by accountants if their training in this area is carried out at an inadequate level are summarized. The main errors are incorrect classification of transactions, the presence of inaccuracies in accounting, overstatement of the tax base. Identified characteristics of IT enterprises (scalability, significant risks, high staff turnover) make additional demands on the organization of accounting. The areas that need the most attention to create the appropriate information support for the management of the IT enterprise are reflected. Prospects for further research are to reveal the impact of these features on the organization and methods of accounting in these enterprises.
Classification of IT enterprises: accounting aspect
Keywords: ІТ-підприємство; ІТ-послуга; ІТ-продукт; ІТ-товар; бухгалтерський облік; бухгалтер; ризик; IT enterprise; IT service; IT product; accounting; IT product; accountant; risk